Formulation of Castor Leaf Extract as a Propestic Pesticide to Control Shallot Caterpillar Pest Spodoptera Exigua Hubn - Adibah, Fatimah; Fauzi, M. Taufik; Sudharmawan, A. A. (Jurnal Biologi Tropis, 2025)
One of the crops that can be cultivated in drylands is shallots. Spodoptera exigua Hubn is the main pest that attacks shallot plants. The purpose of writing this article is to review the results of previous research on jatropha leaves as a vegetable peticide with various extracts so that it can be known which extract is the most optimal as a control of onion caterpillar pests. The method used in this writing is to collect and process data sources from previous research published in scientific articles, books, and discussion results.  The results showed that active compounds such as saponins, flavonoids, alkaloids, tannins, and phenols in Jatropha leaves extract significantly increased pest mortality and decreased pest feeding activity. Higher  extract concentrations were directly proportional to greater negative effects on pests, highlighting the potential of falak nut leaves as an effective and environmentally friendly plant-based pesticide.